The gift as material culture report of a Yale-Smithsonian seminar held at the Smithsonian Institution, Washington, D.C., April 28-30, 1991 - Thatcher, Patricia; Taylor, Paul Michael 1953- (Yale-Smithsonian Seminar on Material Culture, 1995)
Introduction: Perspectives on the gift in Indonesia and beyond / Paul Michael Taylor -- Wedding gifts and marital alliances -- Gifts in economic perspective -- Power and propitiation: political and religious aspects of gift giving -- Conclusion and questions for further study
Includes bibliographical references
Keywords: Alltag, Brauchtum; Gifts / Congresses; Ceremonial exchange / Congresses; Gifts / Congresses / Indonesia; Ceremonial exchange / Congresses / Indonesia; Gabe; Geschenk; Sachkultur; Indonesia / Social life and customs / Congresses; Konferenzschrift -- 1991 -- Washington, DC